Reduced CD4+T Cell CXCR3 Expression in Patients With Allergic Rhinitis - Yu, Xiaofeng; Wang, Meng; Cao, Zhiwei (Frontiers in Immunology, 2020)
While T cells are considered to play a primary role in IgE-mediated atopic diseases, little is known about the systemic variations of T cell subsets from patients with allergic rhinitis (AR). To elucidate the characteristics of peripheral T cells, we analyzed natural killer, B cell, and T cell populations, performed T cell subset construction, and assessed chemokine receptor and associated serum cytokine expression in 25 AR patients and 20 healthy controls. Our results revealed increased levels of CD4+T cells, serum interleukin (IL)-10, IL-6, and interferon (IFN)-γ, and reduced Th1 and Th17 subsets, identified by their chemokine receptors, in AR patients. These results suggest a systemic activation of T cell responses in AR. We further demonstrated that AR patients exhibit significantly reduced CD4+T cell CXCR3 expression, especially in patients with moderate-severe disease severity, demonstrating that CXCR3 is a potential key molecule that hinders the Th1/Th2 balance in AR pathology. Overall, systemic T cell activation occurred in AR patients and CXCR3 dramatically decreased in CD4+T cells, which may ultimately be used as a disease biomarker and/or therapeutic target.